Analisis Faktor Penghambat Pelaksanaan Latihan UKM Sepakbola di Universitas PGRI Yogyakarta - Rivo Lahua Praseta; Agus Pribadi; Andri Arif Kustiawan; Bimo Alexander (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to identify internal and external obstacles affecting soccer club training at PGRI University Yogyakarta. It utilized a quantitative descriptive approach, collecting data through validated and reliable questionnaires. The participants were 30 members of the PGRI University Yogyakarta Soccer Club. Data analysis involved descriptive statistics using percentages. The findings indicated that internal factors hinder 86% of training, categorized as moderate, while external factors impede 53%, also in the moderate category.